ANALISIS HUBUNGAN FAKTOR INTERNAL DAN EKSTERNAL TERHADAP KELELAHAN KERJA SELAMA PANDEMI COVID-19 PADA PEKERJA PROYEK CENDRAWASIH TERRACE BINTARO PT. ADHI PERSADA GEDUNG - Nurunnisa Paquita Syech Abu Bakar (2021)
Work-related fatigue is physical and mental conditions decreasing work endurance. Internal and external factors may cause it. The construction industry is one of the jobs where its workers are prone to fatigue. Its tight schedule forces the project leader to demand higher performance from field workers, particularly during the COVID-19 pandemic. This study aimed to assess the relationship of internal factors (age, nutritional status, sleep quantity, disease history) and external factors (working hours, working shift, working tenure) on work-related fatigue on workers of the Cendrawasih Terrace project. This study employed a quantitative method with a cross-sectional design. The study population was 90 people, where the samples were selected based on the total sampling technique. Data collection was performed using a questionnaire. The Chi-Square result states a significant relationship between age (p-value 0,000), nutritional status (p-value 0,007), sleep quantity (p-value 0,015), working hours (p-value 0,008), and working tenure (p-value 0,017) with work-related fatigue. Meanwhile, disease history and working shift had no relationship with work-related fatigue on workers of the Cendrawasih Terrace project. The recommendations are considering the working unit division based on physical endurance and age, re-evaluating working hours following the regulation, and arranging the overtime system well. Keywords : Work-related Fatigue, Construction, Risk Factors